Smartphones and Patient Care: Exploring the Use of Text-Based Messaging for Patient-Related Communication. (June 2016) - Goldfarb, Jeremy; Kayssi, Ahmed; Devon, Karen; Rossos, Peter G.; Cil, Tulin D.
Background . Text messaging (texting) has become a routine medium of communication in society. However, its use among clinicians has not been fully characterized. We explored general surgery residents' practices and views on texting for patient-related communication. Methods . An email survey was distributed to all general surgery residents at a large Canadian medical school. Results . Overall, 46 (57%) of those surveyed responded. All used texting for patient-related communication. Eleven percent of residents did not have a password on their cell phone and 89% did not have encrypted phones. Texting was the most common way (41%) by which residents communicated routine patient-related information with staff physicians. Most (85%) residents agreed that texting enhances patient care. The majority (66%) did not know if their hospital had a policy on texting and were unaware of legislation surrounding texting in patient care (89%). Conclusions . Most general surgery residents use texting for communication of routine patient-related care issues. However, they acknowledge concerns regarding the security of this medium.